2009
DOI: 10.1063/1.3141751
|View full text |Cite
|
Sign up to set email alerts
|

Control of the charge-ordering-insulating phase in epitaxial La1−xCaxMnO3 (x=0.30–0.45) thin films under the anisotropic strain

Abstract: Articles you may be interested inEffect of growth oxygen pressure on anisotropic-strain-induced phase separation in epitaxial La0.67Ca0.33MnO3/NdGaO3 (001) films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Compared with the pseudocubic structure of LCMO at the given doping level, NGO(0 0 1) substrates supply a suitable edge length [3.865Å for LCMO and 3.867Å for NGO(0 0 1)], but a notable in-plane angle mismatch [89.8641 for LCMO and 89.2651 for NGO(0 0 1)] for the unit cells, producing a large shear strain, or anisotropic strain in orthorhombic notation, for coherent LCMO/ NGO(0 0 1) films [7,15]. To check the structural quality, all the films have been examined by XRD linear scans around the (0 0 2) reflections, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the pseudocubic structure of LCMO at the given doping level, NGO(0 0 1) substrates supply a suitable edge length [3.865Å for LCMO and 3.867Å for NGO(0 0 1)], but a notable in-plane angle mismatch [89.8641 for LCMO and 89.2651 for NGO(0 0 1)] for the unit cells, producing a large shear strain, or anisotropic strain in orthorhombic notation, for coherent LCMO/ NGO(0 0 1) films [7,15]. To check the structural quality, all the films have been examined by XRD linear scans around the (0 0 2) reflections, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During deposition the temperature and oxygen pressure were fixed at 735 1C and 45 Pa, respectively, and the laser energy density and repetition rate were kept at 2 J/cm 2 and 5 Hz, respectively, resulting in a growth rate of about 6 nm/min. After the growth all the samples were ex-situ annealed at 780 1C in flowing O 2 gas for 5 h, so as to get the various PS states instead of the FMM ground state as verified for all the as-grown films or the bulk counterparts [7]. The magnetotransport properties were measured using the four-probe method on a Quantum Design physical property measurement system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,32 The ceramic LCMO target was prepared by standard solid state reactions. During deposition, the substrate temperature and O 2 pressure were 735…”
Section: Methodsmentioning
confidence: 99%
“…More strikingly, though the bulk LCMO is optimally doped in the ferromagnetic-metal (FM) ground state, the LCMO/NGO(001) films, after being annealed in oxygen atmosphere, show an antiferromagnetic insulator phase transition at ∼250 K and the PS with the coexistence of antiferromagnetic-insulating (AFI) and FM phases at the temperature below. [32][33][34][35] In the early work we have demonstrated that the ex-situ annealing process and the NGO(001) substrate stabilized in-plane anisotropic strain state are both indispensable for the formation of AFI phase. 34,35 However, the detailed evolutions of the strain state and octahedral behavior during annealing, which are central for understanding the AFI phase and PS, are still unclear.…”
Section: Introductionmentioning
confidence: 99%